Dinucleotide (CA)n tandem repeats on the human X-chromosome and the history of the Mediterranean populations - Josep Santamaría; Miguel M. Álvarez-Álvarez; M. Esther Esteban; Elies Ramon-Gurrea; Pedro Moral (Taylor & Francis Group, 2018)
Background: Tandem repeats (STRs) are genomic markers of particular interest in forensic and population genetics. Most of the population data currently available correspond to the variation of STRs of forensic panels, which barely include dinucleotide tandem repeats. Aims: The aim of the study is to test the usefulness of a battery of dinucleotide STRs on the X chromosome for population and forensic studies. Subjects and methods: A total of 672 individuals from 12 Mediterranean populations and two external references were analysed for 15 X-STR following the instructions of the commercial company and using control DNA from the CEPH centre whose sequences are published in GenBank. Genotypic results were analysed using standard population genetics methods including estimates of linkage disequilibrium, population structure and gene flow. Common forensic efficiency parameters were calculated. Results: The analysed X-STRs show high values of genetic diversity, comparable to other STRs of more common use. No significant associations between markers were found. A slight population structure was detected between the two shores of the Mediterranean. The X-STRs studied here present a similar degree of variability to that of other X-STRs used in forensics. Conclusion: Tandem-repeated dinucleotides are a good tool for evidencing population differences here. Forensic parameters indicate that the dinucleotide X-STRs are suitable for forensic use.